Research and Technological Innovation The Challenge for a New Europe - Quadrio Curzio, Alberto; Fortis, Marco; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2005)
To explain the importance of scientific research and technological innovation for industrial countries and in particular for the EU, in order to improve or to maintain economic leadership, is the central idea of this volume. It starts with a historical and theoretical perspective on scientific-technological innovation and its importance for industrial growth. Then it analyzes EU policy framework and strategies for R&D and it presents several national success stories both from EU and non-EU countries to confirm the theoretical perspective. .
- Research, Technology, Innovation: Analysis and Cases -- Scientific-Technological Innovation and Industrial Growth -- The Intellectual Origins of Modern Economic Growth -- Local Systems and Networks in the Globalisation Process -- The Dynamics of High-Tech Clusters: Competition, Predation, Synergies -- High-Technology Clusters: Specialisation and Interaction -- New Industry, European Framework and National Success Stories -- New Science, New Industry and New Institutions? Second Thoughts on Innovation and Europe$1 (Bs Universities -- EU Strategies for Research and Development -- Aiming at the Barcelona Target: Best Practices and National Performances. The EASAC Perspective -- The Locational Dynamics of the U.S. Biotech Industry: Knowledge Externalities and the Anchor Hypothesis -- The Cambridge Phenomenon -- Knowledge Capital and Economic Growth: Sweden as an Emblematic Example -- Relationships between Universities, Research Centers and District Firms: the Italian Case.s
Keywords: Economic policy; Economics; R & D/Technology Policy; Economic Policy; Electronic books